Genotypic and phenotypic characterization of Escherichia coli isolated from mollusks in Brazil and the United States. Issue 5 (11th October 2018) - Miotto, Marília; Ossai, Sylvia A.; Meredith, Joan E.; Barretta, Clarissa; Kist, Airton; Prudencio, Elane S.; R. W. Vieira, Cleide; Parveen, Salina
Abstract: The aim of this study was to determine the serogroups, antimicrobial resistance and genetic diversity of Escherichia coli isolates from samples of bivalve mollusks collected along Santa Catarina coast, Brazil, and from the Chesapeake Bay, Maryland, USA. One hundred forty‐one E. coli isolates were characterized for serogroups with 181 specific O antisera and antimicrobial susceptibility using the disk diffusion method. The genetic diversity was assessed using pulsed‐field gel electrophoresis (PFGE). The results showed that among the isolates, 19.9% were classified as multi‐drug resistant (MDR) and resistance was most frequently observed to cephalothin, nitrofurantoin, and ampicillin. The predominant serogroups were O6, O8, and O38. Some serogroups were recognized as pathogenic E. coli . PFGE dendrograms indicated extensive genetic diversity among the isolates. Although characteristics of the E. coli isolates were highly variable, it is important to note that E. coli belonging to pathogenic serogroups and MDR isolates are present in mollusks of both study areas. This is the first report on the phenotypic and genotypic characterization of E. coli from mollusks from Santa Catarina and the Chesapeake Bay that should encourage studies focusing on comparison of isolates across countries. Abstract : The aim of this study was to determine the serogroups, antimicrobial resistance, and genetic diversity of Escherichia coli isolates from samples of bivalve mollusks collected along Santa Catarina coast, Brazil, and from the Chesapeake Bay in Maryland, USA. Some serogroups found in this study were pathogenic E. coli strains, and the MDR isolates provide evidence that emphasizes the problems related with overuse of antimicrobials. This is the first report on the phenotypic and genotypic characterization of E.coli from mollusks from Santa Catarina coast and the Chesapeake Bay.